2021
DOI: 10.3390/molecules26164826
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory, Antipyretic, and Analgesic Properties of Potamogeton perfoliatus Extract: In Vitro and In Vivo Study

Abstract: Natural antioxidants, especially those of plant origins, have shown a plethora of biological activities with substantial economic value, as they can be extracted from agro-wastes and/or under exploited plant species. The perennial hydrophyte, Potamogeton perfoliatus, has been used traditionally to treat several health disorders; however, little is known about its biological and its medicinal effects. Here, we used an integrated in vitro and in vivo framework to examine the potential effect of P. perfoliatus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Carrageenan induced acute inflammation was evidenced by the appearance of paw edema in rats. Carrageenan-induced rat paw edema is a well-established animal model to evaluate the anti-inflammatory properly of phytochemicals [ 10 , 21 ]. The edema volume was sharply increased 1 h after injection (38%) and reached maximum size by 5/6 h (52%) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Carrageenan induced acute inflammation was evidenced by the appearance of paw edema in rats. Carrageenan-induced rat paw edema is a well-established animal model to evaluate the anti-inflammatory properly of phytochemicals [ 10 , 21 ]. The edema volume was sharply increased 1 h after injection (38%) and reached maximum size by 5/6 h (52%) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Carrageenan, a highly sulfated polysaccharide is widely used as food additive due to its capability to enhance the food structure [ 31 ]. Carrageenan (non-antigenic phlogistic agent)-induced rat paw edema is a well-established and widely used model to evaluate the anti-inflammatory properly of plant and synthetic compounds [ 10 , 21 ]. Carrageenan-induced edema development is a biphasic acute inflammatory response [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neuropathic pain and neuroinflammation are often linked with the nerve injuries like scientic nerve injury (Myers et al, 2006;Ellis and Bennett, 2013;Mahmoud et al). Literature suggested that Potamogeton perfoliatus L. inhibiting 5-lipoxygenase and cyclooxygenase-2 enzymes, and thus possessing potential antiinflammatory and analgesic properties (Rezq et al, 2021).…”
mentioning
confidence: 99%